Effects of pretreatment of ethanolic extract of Siegesbeckia pubescens Makino on cerebral ischemia in rats - Muhammad Naveed; Rahat Ullah; Sobia Noreen; Muhammad Saeed; Gang Sheng; Hafiz Muhammad Zubair; Zhou Xiaohui (Elsevier, 2022)
Background: Cerebral ischemia is characterized by inadequate blood supply to the brain to fulfill its metabolic demand. It is a leading cause of stroke. The objective of this study aimed to elucidate the effects of ethanolic extract of Siegesbeckia pubescens (EESP) Makino against cerebral ischemia in rats. Methods: Sixty male Sprague-Dawley (SD) rats were distributed into 5 groups (n = 12) viz., low dose (2.5 g/kg/day) EESP group, high dose (5 g/kg/day) EESP group, Nimodipine group, untreated control, and sham-operated control. The reference group received 16 mg/kg/day of nimodipine, while the untreated and sham-operated control was given 20 ml/kg of distilled water. The middle cerebral artery occlusion (MCAO) induced focal cerebral ischemia. On the 7th day of the trial, neurological evaluation and biochemical assays were carried out. After that, rats were sacrificed, and the brain infarct area was analyzed with image processing software. Results: The extent of neurologic deficits, infarct area, concentration of superoxide dismutase (SOD), and malondialdehyde (MDA) was significantly altered by the EESP when compared with untreated control and Sham-operated control. Conclusions: Taken together, these results reported protective effects of EESP on cerebrovascular ischemia that perhaps correlate with its mechanism of free radical scavenging. Our findings may provide insight into treating cerebral ischemia and give a new research era for further study.